Delayed disease progression in HIV‐2: the importance of TRIM5α and the retroviral capsid - Boswell, M. T.; Rowland‐Jones, S. L. (Clinical and experimental immunology, 2019)
Summary HIV‐2 is thought to have entered the human population in the 1930s through cross‐species transmission of SIV from sooty mangabeys in West Africa. Unlike HIV‐1, HIV‐2 has not led to a global pandemic, and recent data suggest that HIV‐2 prevalence is declining in some West African states where it was formerly endemic. Although many early isolates of HIV‐2 were derived from patients presenting with AIDS‐defining illnesses, it was noted that a much larger proportion of HIV‐2‐infected subjects behaved as long‐term non‐progressors (LTNP) than their HIV‐1‐infected counterparts. Many HIV‐2‐infected adults are asymptomatic, maintaining an undetectable viral load for over a decade. However, despite lower viral loads, HIV‐2 progresses to clinical AIDS without therapeutic intervention in most patients. In addition, successful treatment with anti‐retroviral therapy (ART) is more challenging than for HIV‐1. HIV‐2 is significantly more sensitive to restriction by host restriction factor tripartite motif TRIM5α than HIV‐1, and this difference in sensitivity is linked to differences in capsid structure. In this review we discuss the determinants of HIV‐2 disease progression and focus on the important interactions between TRIM5α and HIV‐2 capsid in long‐term viral control. HIV‐2 is significantly more sensitive to restriction by host restriction factor TRIM5α than HIV‐1, and this difference in sensitivity is linked to differences in capsid structure. In this review we discuss the determinants of HIV‐2 disease progression and focus on the potential importance of the interactions between TRIM5α and HIV‐2 capsid in long‐term viral control.